INFLUENCE OF NANOSIZED CERIUM DIOXIDE ON THE VASCULAR BED OF THE LIVER UNDER THE CONDITIONS OF CHRONIC ALCOHOLIC HEPATITIS MODELING - Mykytenko, A.O.; Akimov, O.Y.; Yeroshenko, G.A.; Neporada, K.S. (World of Medicine and Biology, 2024)
Chronic alcohol consumption changes the microcirculation of the liver and, depending on the duration and dose of ethanol, can have various negative consequences. Nanosized cerium dioxide can be an effective means of pathogenetic correction of ethanol-induced changes in the liver. The aim of the work was to study the effect of nanosized cerium dioxide on the morphometric indicators of the vascular bed of rat liver under the conditions of chronic alcoholic hepatitis modeling. The experiments were performed on 24 white, mature male Wistar rats, weighing 180–220 g. Animals modeled chronic alcoholic hepatitis according to Stepanov Yu.M. (2017) and nanosized cerium dioxide was administered intragastrically at a dose of 1 mg/kg in a volume of 2.9 ml/kg. The morphometric parameters of the inner diameter of the vessels of the liver lobe were determined; capillary lumen around the central vein and hepatic triad. Simulation of chronic alcoholic hepatitis leads to expansion of the central vein and narrowing of interlobular arteries and veins and lobular arterioles and venules. The introduction of nanodispersed cerium dioxide against the background of modeling chronic alcoholic hepatitis expands alcohol-narrowed lumens of interlobular arteries and veins and lobular arterioles and venules, without affecting the diameter of the central vein.
Keywords: nanosized cerium dioxide; vascular bed; chronic alcoholic hepatitis; liver; rats